2015
DOI: 10.1021/acsami.5b05860
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Thermoelectric Properties of a Conducting Polymer through Blending with Open-Shell Molecular Dopants

Abstract: PSS that persist despite the highly acidic environment that occurs due to the presence of the poly(styrenesulfonate) moiety. Additionally, the oxidation-reduction-active (redox-active) nature of the TEMPO-OH small molecules provides a means by which to filter charges of different energy values. Therefore, these results demonstrate that a synergistic combination of an open-shell species and a conjugated polymer allows for enhanced thermoelectric properties in macromolecular systems, and as such, it offers the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…The first was the de-doping process through tuning the charge carrier concentration along the polymer chains. Bubnova et al reported the use of tetrakis(dimethylamino)ethylene to tune the electron distribution along PEDOT: p -toluenesulfonate (PEDOT:Tos) to enhance electrical conductivity significantly (Bubnova et al, 2011; Tomlinson et al, 2015). The second approach is the secondary doping with organic solvents or counter-ions so as to tune the polymer chain conformation.…”
Section: Resultsmentioning
confidence: 99%
“…The first was the de-doping process through tuning the charge carrier concentration along the polymer chains. Bubnova et al reported the use of tetrakis(dimethylamino)ethylene to tune the electron distribution along PEDOT: p -toluenesulfonate (PEDOT:Tos) to enhance electrical conductivity significantly (Bubnova et al, 2011; Tomlinson et al, 2015). The second approach is the secondary doping with organic solvents or counter-ions so as to tune the polymer chain conformation.…”
Section: Resultsmentioning
confidence: 99%
“…DMSO with NaOH dedoping ~15.8 ~785 ~19.6 [120] Post DMSO + Hydrazin dedoping 49.3 1310 318.4 [115] Sorbitol + TDAE dedoping 27.47 ~295 ~22.3 [111] HI + DMSO (post treatment) ~30.8 ~475 ~45.1 [114] DMSO and Sorbitol 11.98 1063 15.3 [121] H2SO4 + NaOH 39.2 2170 333.5 [91] Multi-layered DMSO 10.6 187 2.1 [122] Salt + DMF 28 1831 143.6 [108] H2SO4 149.47 65.82 147.1 [123] DMSO and EMIMBF4 post treatment ~23.5 ~680 ~37.6 [124] TEMPO-OH ~22.5 ~33 ~1.7 [125] Depicted in Figure 10 is a collection of thermopower-conductivity data from literature obtained for PEDOT:PSS subjected to different treatments; for completeness also data for the PEDOT:Tos system are plotted. As noticed before, the majority of the data does not follow the empirical -¼ power-law relationship between conductivity and thermopower observed for most doped thiophenes and other doped polymers.…”
Section: Pedot:pssmentioning
confidence: 99%
“…Collection of various thermopower-conductivity data from literature as indicated in the legend. [6,7,91,111,[123][124][125]127] The grey line indicates a power law with slope -1/4, the black solid line is a fit to the transport edge model Eq. 11 (same parameters as in Figure 3c of Ref.…”
Section: Pedot:pssmentioning
confidence: 99%
“…Efforts have been made in improving the TE performance of the PEDOT:PSS films, including both the electrical conductivity and Seebeck coefficient. One straightforward way is to enhance the electrical conductivity of PEDOT:PSS by a post‐treatment with chemical agents such as organic polar solvents, acids, and small molecules . In terms of the fundamental physics, Seebeck coefficient depends on the energy band structure and the density of states (DOS) of the TE materials.…”
Section: Introductionmentioning
confidence: 99%